Analysis of the diagnostic accuracy of rapid antigenic tests for detection of SARS-CoV-2 in hospital outbreak situation - Aranaz Andrés, Jesús María; Fernández Chávez, Abelardo; McGee-Laso, Amaranta; Melanie Abreu, Paloma; Galán, Juan Carlos; Cantón, Rafael (Springer Science and Business Media Deutschland GmbH, 2022)
The reverse transcriptase polymerase chain reaction (RT-PCR) continues to be the reference diagnostic method for the confirmation of COVID-19 cases; however, rapid antigen detection tests (RADT) have recently been developed. The purpose of the study is to assess the performance of rapid antigen-based COVID-19 testing in the context of hospital outbreaks. This was an observational, cross-sectional study. The study period was from October 2020 to January 2021. The “Panbio COVID-19 AG” RADT (Abbott) was performed and TaqPath COVID-19 test RT-PCR. The samples were obtained from hospitalised patients in suspected outbreak situations at the Ramón y Cajal Hospital. A hospital outbreak was defined as the presence of 3 or more epidemiologically linked cases. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the RADT were calculated using RT-PCR as a reference. A total of 17 hospital outbreaks were detected in 11 hospital units during the study period, in which 34 RT-PCR and RADT screenings were performed. We obtained 541 samples, which were analysed with RT-PCR and a further 541 analysed with RADT. Six RADT tests gave conflicting results with the RT-PCR, 5 of them with a negative RADT and positive RT-PCR and one with positive RADT and a negative RT-PCR. The sensitivity of the RADT was 83.3% (65.3–94.4%) and the specificity was 99.8% (98.9–100%). The PPV was 96.2% (80.4–99.9%) and the NPV was 99% (97.7–99.7%). The RADT shows good diagnostic performance in patients on non-COVID-19 hospital wards, in the context of an outbreak.
Keywords: asymptomatic screening; COVID-19; rapid antigen tests; Scopus; JCR